2021
DOI: 10.3390/su13084329
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Designing Mixed Light-Emitting Diodes to Match Greenhouse Plant Absorption Spectra

Abstract: We report a methodological approach for simulating luminary output radiation, which is achieved by mixing light-emitting diodes (LEDs) in order to match any plant absorption spectrum. Various recorded narrow-band LED spectra of different colors were first characterized and then fitted with a multi-Gaussian model. An optimizing procedure computed the optimal weighting of the relevant parameters so as to minimize the discrepancy between the combined spectrum and the reference target curve. The particle swarm opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The Special Issue, entitled "The Future of Interior Lighting Is Here", addressed several subjects on interior lighting such as architectural lighting, daylighting, Human Centric Lighting (HCL), the impact on human health, lighting design, sustainability, and social impact and wellbeing. A total number of eleven articles, ten research papers [24][25][26][27][28][29][30][31][32][33] and one review paper [34], were published. In terms of the geographical distribution of the affiliations of the 34 contributing authors, contributions originated from ten countries, including Austria, Denmark, France, Germany, Korea, Slovakia, Spain, Sweden, Tunisia, and UK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Special Issue, entitled "The Future of Interior Lighting Is Here", addressed several subjects on interior lighting such as architectural lighting, daylighting, Human Centric Lighting (HCL), the impact on human health, lighting design, sustainability, and social impact and wellbeing. A total number of eleven articles, ten research papers [24][25][26][27][28][29][30][31][32][33] and one review paper [34], were published. In terms of the geographical distribution of the affiliations of the 34 contributing authors, contributions originated from ten countries, including Austria, Denmark, France, Germany, Korea, Slovakia, Spain, Sweden, Tunisia, and UK.…”
Section: Methodsmentioning
confidence: 99%
“…Bachouch et al [29] reported a methodological approach for simulating luminaires' spectrum for greenhouse plants. That was achieved by mixing LED chips in an effort to match the absorption spectrum of any plant.…”
Section: Light Distribution and Spectrummentioning
confidence: 99%
“…Using Grassmann's color mixing theory, phosphor coated warm white LED source (CCT 2800 K) is mixed with the blue (467 nm) and green (527 nm) LED light sources and a detailed mathematical formulation is derived for easy controlling of variable CCT and experimentally validated (Wu et al 2017). Bachouch et al (2021)reported a methodological approach for simulating luminary output radiation, which is achieved by mixing light-emitting diodes (LEDs) in order to match any plant absorption spectrum. Various recorded narrow-band LED spectra of different colors were first characterized and then fitted with a multi-Gaussian model.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous approaches that require multiple measurements with a spectrometer or a reference color chart under a target illumination environment, our method requires no additional information for the spectral upsampling step (Das & Mazumdar 2021) Chen et al ( 2022) reported a design method for a high-power optical system based on RGB LED Arrays with multiple channels to achieve highquality color-mixing and uniform lighting. The highpower optical system consists of a multi-channel reflector and a color-mixing component (Bachouch et al 2021). Onwukaeme, Lee and Ryu (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Bachouch et al reported a methodological approach for simulating luminary output radiation, which is achieved by mixing light-emitting diodes (LEDs) to match any plant absorption spectrum. Various recorded narrowband LED spectra of different colors were first characterized and fitted with a multi-Gaussian model [11]. Liu et al used the double Gaussian model to describe the SPD of a single GaN chip or a single QD system.…”
mentioning
confidence: 99%